PENGARUH CITRA MEREK, KUALITAS LAYANAN, DAN HARGA TERHADAP KEPUASAN PENGGUNA JASA PENGIRIMAN J&T EXPRESS DI DROP POINT KRAKATAU MEDAN - Sofi Adinda Amri Nasution; Yayuk Yuliana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2022)
This study aims to examine the effect of brand image (X1), service quality (X2), and price (X3) on user satisfaction (Y) of J&T Express delivery services at Drop Point Krakatau Medan. The data used is primary data using probability sampling method, with a total sample of 98 respondents. The analysis method of this research uses multiple linear regression. The classical assumption test used has met the specified criteria, the t-test (partial test) shows that the brand image, service quality, and price variables have a positive and significant effect on user satisfaction because the tcount > ttable of brand image is 10.606 > 1.664, the tcount > ttable of service quality is 2.874 > 1.664 and tcount > ttable of price is 11.808 > 1.664. From the results of the f test (simultaneous test) the value of fcount > ftable is 60.545 > 3.09, then this shows that brand image, service quality and price together have a significant effect on satisfaction of J&T Express service users at Drop Point Krakatau Medan